Pregnancy associated atypical hemolytic uremic syndrome triggered by massive uterine bleeding after outpatient dilatation and evacuation. Issue 1 (June 2022) - Tran, Minh-Ha; Penalosa, Patrick; Hamiduzzaman, Anum; Hanna, Ramy
Background: Atypical Hemolytic Uremic Syndrome (aHUS) is a renal threatening multi-system disorder with significant hematologic findings of microangiopathic hemolytic anemia (MAHA) and thrombocytopenia. Early recognition and institution of late complement inhibitors can interrupt a cycle of progressive hemolysis and renal injury. Methods: We present an informative case of aHUS triggered by pregnancy termination. Diagnostic, laboratory, and treatment measures are reviewed. Results: Clinical evidence demonstrates immediate improvement in hemolysis, platelet consumption, and acute kidney injury following initiation of eculizumab. Conclusion: Pregnancy is a recognized trigger of aHUS and its proper management requires early recognition and institution of late complement blockade. Genetic testing can be sent for genetic counseling purposes, but initiation of treatment should neither await these results nor be discontinued when high-risk polymorphisms are absent.